PERAN LITERASI MEDIA DALAM MEMAKNAI PESAN PEMASARAN POLITIK - Riefky Krisnayana (Dialektika, 2017)
The phenomenon of the impact of internet technology on the political attitude of the public affects politicians in Indonesia. Politics is now a product that needs to be marketed as well as in commercial marketing. Through the imagery is expected to move the opinion to a better direction. With positive public opinion, the decision to vote becomes a necessity for politicians who are fighting in the political arena. Public opinion itself is a method of persuasion with a communication system through digital media that is direct and massive and can provide viral effects. Imagery becomes a very important part of the political marketing system. Political marketing itself is a practical method in the context of political communication, so it needs a media literacy movement designed to increase individual control over the media they use in interpreting the message.